Research on nonhuman primates - Hendrickx, Andrew G. (Advances in veterinary science and comparative medicine, 1984)
Advances in Veterinary Science and Comparative Medicine, Volume 28: Research on Nonhuman Primates covers topics on biomedical research in primates. The book discusses the techniques of paternity exclusion analysis using technology to identify phenotypes for a large number of genetic loci, as well as the importance of behavioral primatology in conserving the nonhuman primate. The text also describes the establishment of the cynomolgus monkey as a laboratory animal; the development of an artificial breeding colony of primates; and the use of primates as animal models for various human health-related problems. The spontaneous and induced obesity in macaques; the relationships of nonhuman primates and other animal models to human forms of diabetes; and viral disease models in primates are also encompassed. Veterinarians, anthropologists, psychologists, microbiologists, and those dealing with comparative medicine and primate research will find the book invaluable.